Plant communities as indicators of anthropogenic disturbance on a peri-urban tropical wetland of Lutembe Bay wetland system, Uganda - Nuubu Takuwa; Eleanor Wozei; Sarah Kizza-Nkambwe; Geoffrey Malinga; George Kilande; Joel Kinobe (Sustainable Environment)
Wetland degradation linked to peri-urban anthropogenic pressures is a major threat to wetland biodiversity. However, little is known of the response of biodiversity to this disturbance. Biotic indicator species are useful for assessing the health and ecological integrity of wetlands. This study evaluated patterns of plant species richness and composition, and determined species characterizing each of three differently disturbed wetland sites of Lutembe Bay Wetland, a peri-urban Ramsar Wetland of International Importance and an Important Bird Area in Uganda. The study revealed that total nitrogen decreased following wetland degradation, but total phosphorous was not affected; pH values were <5.5, while OM content was low in the lightly and heavily (2.5–4.4%) degraded sites. While plant species richness did not differ among the sites, total species richness was higher in heavily disturbed, compared to lightly disturbed and relatively intact sites. Community composition differed significantly among the three sites. Indicator plant species were then identified which could be employed as a rapid assessment tool to infer the level of degradation in the sustainable management of Afrotropical wetlands by practitioners. Results show that continued unsustainable use of wetlands results in changes in soil properties and plant species composition, highlighting the need to restore anthropogenically disturbed parts of wetlands and to prevent further degradation of less degraded areas.